Policy Implementation Analysis: Examining the Effectiveness of Jambi's Teacher Certification Program - Haesdhona; Mukti Diapepin; Donna Ikranova Febrina; Mardiansyah; Hamirul (Enigma in Education, 2024)
Teacher quality is crucial for improving education outcomes. Indonesia introduced the Teacher Certification Program (Sertifikasi Guru) in 2005 to enhance teacher professionalism. This study investigates the program's effectiveness in Jambi Province by analyzing its impact on teacher competencies, teaching practices, and student learning outcomes. This mixed-methods study involved 300 certified and 300 non-certified teachers in Jambi Province. Quantitative data were collected through questionnaires and student achievement records, analyzed using descriptive statistics, t-tests, and regression analysis. Qualitative data were gathered through interviews with 30 teachers, 10 school principals, and 5 education officials, and analyzed thematically. Certified teachers exhibited significantly higher pedagogical knowledge, subject matter knowledge, and classroom management skills than non-certified teachers. They were also more likely to employ active learning and student-centered approaches. However, the impact on student learning outcomes was modest. In conclusion, Jambi's Teacher Certification Program successfully improved teacher competencies and teaching practices. However, further efforts are needed to enhance its impact on student learning outcomes. Recommendations include strengthening the program's focus on practical application, providing ongoing professional development, and increasing school-level support for effective teaching.